Qur'anic Perspective on Social Religious Conflict Resolution Based on Culture of Togetherness and Rembugan in Indonesia - Mukhtar, Naqiyah; Triana, Nita (Letiges, 2023)
This study described the resolution of religious and social conflicts in Bantarkawung, Central Java, Indoensia; its contributing factors and how they aligned with the Qur'an's perspective. This study employed a qualitative approach by conducting interviews with participants in conflict resolution. During the Covid-19 period from 2020 to 2021, we collected data. This study found that the local government and religious leaders resolved conflicts based on the culture of togetherness in religious rituals and social works, fostering interactions and adhering to consensus-based